3D printed structures for impact energy dissipation - Muhammad Aidil Juhari (2017)
The function of a bicycle helmet is to dissipate energy upon collision. It achieves this with two main components: the helmet foam liner and the hard outer shell. This report focused on improving the energy dissipation mechanisms of the helmet foam liner. Bicycle helmet designs are subjected to rigorous test standards, e.g. CPSC, ASTM, Snell B95 before they are released into the market. Drop impact tests, where the helmets are strapped onto headforms and released onto an anvil from a specific height, are the main tools to evaluate the impact resistance of the helmet. The linear acceleration is recorded and evaluated to determine the peak force acting on the headform. Expanded polystyrene (EPS) foam is currently used in most helmet foam liners due to its superior energy absorption characteristics. However, the rise of additive manufacturing has enabled designers to explore novel materials such as auxetic structures which have negative Poisson’s ratio. A review of auxetic structures revealed that these structures exhibit good energy-absorption properties and higher indentation resistance to conventional materials. Also, the properties of auxetic structures can be controlled by manipulating its geometry. The objective of this paper is to study and investigate the effect of a foam liner for bicycle helmet composed of additively manufactured metamaterial on impact resistance and damage development upon impact. This is done by simulating drop impact tests of 98 J energy in the Finite Element software, ABAQUS/ Complete Abaqus Environment (CAE) Version 2016 Student Edition. The relative density and Poisson’s ratio were varied by controlling the geometry configuration. Subsequently, the linear acceleration and foam crush depth from the impact tests were measured and compared. An important finding in this paper was that a particular configuration, A1, with 20 mm of foam showed 20% reduction in peak linear acceleration with only 6 mm increase in thickness over the original 30 mm of EPS 48 foam.